2020
DOI: 10.1007/s10734-020-00520-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting key educational outcomes in academic trajectories: a machine-learning approach

Abstract: Predicting and understanding different key outcomes in a student’s academic trajectory such as grade point average, academic retention, and degree completion would allow targeted intervention programs in higher education. Most of the predictive models developed for those key outcomes have been based on traditional methodological approaches. However, these models assume linear relationships between variables and do not always yield accurate predictive classifications. On the other hand, the use of machine-learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 70 publications
2
22
0
2
Order By: Relevance
“…The researchers concluded that the model they proposed could be used to determine academically unsuccessful student. Musso et al, (2020) proposed a machine learning model based on learning strategies, perception of social support, motivation, socio-demographics, health condition, and academic performance characteristics. With this model, he predicted the academic performance and dropouts.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The researchers concluded that the model they proposed could be used to determine academically unsuccessful student. Musso et al, (2020) proposed a machine learning model based on learning strategies, perception of social support, motivation, socio-demographics, health condition, and academic performance characteristics. With this model, he predicted the academic performance and dropouts.…”
Section: Literaturementioning
confidence: 99%
“…In the literature, the prediction of academic performance was made with many and various variables, various digital traces left by students on the internet (browsing, lesson time, percentage of participation) (Fernandes et al, 2019;Rubin et al, 2010;Waheed et al, 2020;Xu et al, 2019) and students demographic characteristics (gender, age, economic status, number of courses attended, internet access, etc.) (Bernacki et al, 2020;Rizvi et al, 2019;García-González & Skrita, 2019;Rebai et al, 2020;Cruz-Jesus et al, 2020;Aydemir, 2017), learning skills, study approaches, study habits (Ahmad & Shahzadi, 2018), learning strategies, social support perception, motivation, socio-demography, health form, academic performance characteristics (Costa-Mendes et al, 2020;Gök, 2017;Kılınç, 2015;Musso et al, 2020), homework, projects, quizzes (Kardaş & Güvenir, 2020), etc. In almost all models developed in such studies, prediction accuracy is ranging from 70 to 95%.…”
Section: Literaturementioning
confidence: 99%
“…Miguéis et al (2018) using a dataset of 2459 higher education students employed naïve Bayes, support vector machine, decision tree, random forest, bagged trees and adaptive boosting trees classifiers to address an academic achievement five classes' problem. Musso et al (2020) called on a 655 university students' dataset and an artificial neural network to deal with a problem of classification between low and high levels of three different measures of AA. Mengash (2020) made use of artificial neural network, decision tree, support vector machine and a naïve Bayes classifiers to anticipate five classes of higher education AA from a sample of 2039 students in order to evaluate the admission criteria of a Saudi University.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For many students, this transition causes stress, anxiety, and insecurity, often leading to poor academic performance. It may also lead to students dropping out [2,3]: the highest dropout rate, in fact, occurs in the first year of university, attributed to student difficulties adapting to a new teaching/learning environment [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%